Calcium-iron-magnesium composite catalyst, preparation method thereof and application of calcium-iron-magnesium composite catalyst in catalyzing pypocholoride to oxidize and degrade organic / inorganic wastewater
The Ca and Mg doping of calcium, iron and magnesium composite catalysts improves the iron ore structure, solves the problem of poor catalytic oxidation effect in hypochlorite oxidation technology, and achieves efficient and economical degradation of wastewater pollutants, and is chemically stable in materials. Good performance and suitable for industrial production.
Patent Information
- Application Number
- CN202411317013.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art uses hypochlorite to oxidize and degrade organic or inorganic wastewater, and has problems of low chemical stability and high cost.
The calcium-ferromagnesium composite catalyst is used to improve the structure of iron ore through Ca and Mg doping strategies, form open channels and oxygen vacancies, improve catalytic activity and chemical stability, and is used to catalyze hypochlorite oxidation and degradation of pollutants.
The oxidative degradation rate is achieved quickly and thoroughly, the hypochlorite utilization rate is high, and the chemical structure is stable, which reduces the cost of catalyst use and improves the reuse effect.
Smart Images

Figure CN119186568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalytic material, in particular to a calcium iron magnesium composite catalyst, and also to a preparation method of the calcium iron magnesium composite catalyst and a method for using the calcium iron magnesium composite catalyst to catalyze hypochlorite oxidation and degradation of organic / inorganic wastewater, belonging to the technical field of wastewater treatment. Background Art
[0002] In recent years, with the rapid development of industrial technology, while it has brought huge economic benefits, it has also brought about environmental pollution problems.
[0003] At present, advanced oxidation is usually used for wastewater containing refractory organic or inorganic substances. Commonly used advanced oxidation methods include photocatalytic oxidation, electrochemical oxidation, persulfate oxidation, ozone oxidation, Fenton oxidation, etc. For example, the literature (Gong Min. TiO 2 / Preparation of magnetic sepiolite composite photocatalyst and its performance and mechanism in treating Cu(Ⅱ)-EDTA wastewater [D]. Xiangtan University, 2015) published the TiO 2 / magnetic sepiolite composite material photocatalytic removal of EDTA-Cu, at pH 4.0, the removal rate is the best, reaching 99.9%, while when pH>7, the removal rate is significantly inhibited; in addition, the removal rate of the photocatalytic material after three repetitions is reduced to 80%. This shows that the light energy utilization rate of the photocatalytic system in the process of treating EDTA-Cu is low, and the reusability and stability of the photocatalytic material are not high, and it is easily affected by metal ions in the solution. The literature (Hu Xinxin. Preparation of Ni / rGO-PAC particle electrode and electrocatalytic treatment of Cu-EDTA wastewater [D]. Beijing Forestry University, 2021.) discloses the use of Ni / rGO-PAC catalytic electrode to remove EDTA-Cu and recover Cu. The treatment time is 360min. When the pH is 2.12, the degradation rate of EDTA-Cu and the recovery rate of Cu are 94.2% and 59%, respectively. When the pH is 9.15, the degradation rate and recovery rate are 80.0% and 76.2%, respectively. The electrochemical oxidation method has high energy consumption, and the removal effect is affected by pH. During the removal process, additional metal ions will be generated at the anode, making it difficult to efficiently recover metal Cu. The literature (Wang Qi, Li Yutong, Liu Yue, et al. Effective removal of the heavy metal-organic complex Cu-EDTA from water by catalytic persulfate oxidation: Performance and mechanisms [J]. Journal of Cleaner Production, 2021, 314.) discloses the use of a persulfate / formate system to oxidatively degrade EDTA-Cu. The treatment time is 90 min and the reaction temperature is 70 ° C. The removal rate is 90.98% at an initial pH of 4.0, and the removal rate is only 67.37% at a pH of 10.0. Persulfate oxidation has good reactivity in a moderately alkaline environment, but it has not shown advantages in the current research on the removal of EDTA-Cu. In addition, during the reaction process, it is necessary to increase the concentration of PS, add metal ions or increase the temperature to improve the removal efficiency, and the coexistence of EDTA in the reaction environment also has a significant impact.The document (Xu Suyun, Yan Ning, Cui Minghao, et al. Decomplexation of Cu(II) / Ni(II)-EDTA byozone-oxidation process[J]. Environmental Science and Pollution Research, 2020, 27(1): 812-822.) discloses the use of ozone oxidation technology to treat EDTA-Cu / Ni in electroplating wastewater, removing 5 mg / L of EDTA-Cu / Ni. When the ozone flow rate is always controlled at 2 L / min and the ozone input rate is 24.79 mg / min, when the pH is 7-9, the removal rate is 96.8%-99.6%, and when the pH is 3-5, the removal rate is still above 90%, but when the pH is above 10, the removal rate drops significantly; in addition, 30 mg / L and 50 mg / L EDTA-Cu / Ni need to react for 200 min and 300 min to achieve a removal rate of more than 99%. The advantage of the ozone method is that the oxidation rate is fast and most of the complexes can be removed in a short time; however, the oxidation performance of ozone is not high, such as long reaction time, O. 3 Reduced utilization, 3 The consumption increases, and it will be affected by the pH value, which will reduce the reaction rate, thus seriously affecting the removal efficiency. The literature (Wu Yang. Experimental study on the treatment of complex copper-nickel electroplating wastewater by electro-Fenton method [D]. Harbin Institute of Technology, 2017.) publicly uses electro-Fenton oxidation method to remove complex copper-nickel electroplating wastewater. The concentration of EDTA-Cu is 50 mg / L. When the electrode is an iron electrode and the reaction conditions are H 2 O 2 Dosage: 6mL / L·h, current density: 10mA / cm 2 , the removal rates of Cu and TOC at pH = 2.0 were 99.02% and 41.84% respectively, while the removal rates at pH = 5.0 were 88.78% and 28.42% respectively; when the electrodes were graphite electrodes and aluminum electrodes, Fe(Ⅱ) was required to be added for the normal reaction process, and the concentration of Fe(Ⅱ) needed to be above 800 mg / L. The Fenton oxidation method requires the addition of chemical reagents, has a high reagent cost, and will also produce a large amount of iron-containing sludge, and cannot effectively recover metal Cu, so it needs to be combined with other processes for treatment, but it is still limited by pH, and there may be higher reagents and more complex removal steps. If the economic cost is controlled, the removal effect will be unstable; the electro-Fenton method has higher removal efficiency and lower reagent cost than the traditional Fenton method, but like the traditional Fenton method, it is greatly affected by pH, and the energy consumption cost is also high, and it is more difficult to recover heavy metal Cu.
[0004] Hypochlorous acid oxidation is a new type of environmentally friendly advanced oxidation technology with the advantages of strong oxidizing ability, wide reaction pH range, high efficiency and economy. Therefore, it is widely used in the degradation of organic matter and the removal of heavy metals. However, its active substance production rate is not high, and its instability will also lead to natural decomposition and reduce the production of active substances. Therefore, it is necessary to add exogenous substances or energy supply to accelerate the production rate of active substances in the reaction process and improve its oxidation performance. For example (Li, Huosheng, et al. "Highly efficient removal of thallium(I)from wastewatervia hypochlorite catalytic oxidation coupled with adsorption by hydrocharcoated nickel ferrite composite." Journal of hazardous materials 388(2020):122016.) The magnetic carbon-coated nickel ferrite composite (NiFe 2 O 4 @C), the composite material is used as a catalyst for the oxidation of hypochlorite (Tl), NiFe 2 O 4 The combination of @C and hypochlorite greatly improves the rate and efficiency of Tl(I) removal, but the catalyst synthesis method is complicated and contains heavy metal nickel. Summary of the invention
[0005] In view of the defects of the prior art, the first object of the present invention is to provide a calcium iron magnesium composite catalyst, which has good chemical stability, high catalytic activity, and avoids the use of harmful transition metals or precious metals. The catalyst is used to catalyze hypochlorite to degrade pollutants in organic or inorganic wastewater, and exhibits the characteristics of fast oxidative degradation rate, thorough oxidative degradation, high hypochlorite utilization rate, etc., so as to solve the problem that the above-mentioned hypochlorite has poor catalytic oxidation effect when being used to remove pollutants that are difficult to oxidize and degrade in organic or inorganic wastewater.
[0006] The second object of the present invention is to provide a method for preparing a calcium-iron-magnesium composite catalyst, which is simple, low in cost, has low requirements on equipment, good operability, and is conducive to industrial production.
[0007] The third object of the present invention is to provide an application of a calcium iron magnesium composite catalyst, which is used to catalyze the degradation of pollutants in organic or inorganic wastewater by hypochlorite, and exhibits the characteristics of fast oxidative degradation rate, thorough oxidative degradation, high hypochlorite utilization rate, etc., and the catalyst has a stable chemical structure in the hypochlorite oxidation system, good reuse effect, and is conducive to reducing the use cost of the catalyst.
[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a calcium-iron-magnesium composite catalyst, which comprises dissolving calcium salt, magnesium salt and iron salt in water, adding a strong alkaline solution to carry out a hydrolysis co-precipitation reaction, and the obtained precipitated product is successively centrifuged, washed, dried and ground to obtain the catalyst.
[0009] The preparation method of the calcium-iron-magnesium composite catalyst of the present invention is to improve the ferrihydrite catalytic material by adopting the Ca and Mg doping strategy to improve its catalytic activity and chemical stability. The doping of Ca and Mg by coprecipitation method changes the agglomeration structure of ferrihydrite and transforms it into a layer block structure, providing open channels and reaction sites. At the same time, the doping of Ca and Mg elements changes the disorder of the crystal structure and the particle size of the material, reduces the binding energy of 2p of Fe and 1s of O, promotes the release of lattice oxygen, thereby forming oxygen vacancies and defects, and the abundant oxygen vacancies can increase the electron transfer ability of the catalytic material surface and promote the generation of active oxygen. Ca and Mg elements replace part of the bond position of the Fe element and form a relatively stable chemical bond with O, so that abundant oxygen vacancies (OVs) are generated on the surface of the material, and the oxygen vacancies (OVs) induced by Ca and Mg doping improve the catalytic performance of the catalytic material, mainly by utilizing its abundant OVs to enhance the electron transfer ability and provide abundant surface adsorption sites, thereby promoting the formation of active oxygen. In the catalytic material catalyzing ClO - During the oxidation process of organic or inorganic pollutants, active oxygen species (singlet oxygen ( 1 O 2 )) plays a major role, among which 1 O 2 The formation comes from the electrons provided by the composite catalyst and ClO - The singlet oxygen generated in the oxidation system plays a key role in the oxidative degradation of organic or pollutants. In particular, the doping of magnesium greatly improves the stability of the catalytic material, greatly improves the chemical stability in the hypochlorite oxidation system, reduces the dissolution of metal ions, and is conducive to improving its cycle stability.
[0010] As a preferred solution, the molar ratio of the calcium salt, the iron salt and the magnesium salt is 1-5:1:0.5-2.5. As the molar ratio of the magnesium salt to the calcium salt relative to the iron salt increases, the catalytic activity of the calcium-iron-magnesium composite catalyst material is significantly improved, and when the molar ratio of the magnesium salt to the calcium salt relative to the iron salt is increased to 1:4 and 1:2 respectively, the catalytic activity of the calcium-iron-magnesium composite catalyst material tends to be stable. Therefore, the molar ratio of the calcium salt, the iron salt and the magnesium salt is further preferably (3-5):1:(1.5-2.5)
[0011] As a preferred solution, the total mass percentage concentration of the calcium salt, magnesium salt and iron salt in water is 1 to 30%.
[0012] As a preferred solution, the calcium salt includes at least one of calcium nitrate, calcium hypochlorite and calcium chloride.
[0013] As a preferred embodiment, the magnesium salt includes at least one of magnesium nitrate, magnesium sulfate and magnesium chloride.
[0014] As a preferred solution, the iron salt includes at least one of ferric chloride, ferric sulfate and ferric nitrate.
[0015] As a preferred solution, the conditions for the hydrolysis coprecipitation reaction are: adding a strong alkaline solution to maintain the pH at 7 to 11, and stirring the reaction at 5 to 40° C. for 0.5 to 3 hours.
[0016] As a preferred solution, the drying is carried out in a vacuum drying manner, the drying temperature is 50 to 75° C., and the drying time is 10 to 20 hours.
[0017] The invention also provides a calcium-iron-magnesium composite catalyst, which is obtained by the preparation method.
[0018] The present invention also provides an application of a calcium-iron-magnesium composite catalyst, which is used for catalyzing the oxidative degradation of hypochlorite into organic and / or inorganic wastewater.
[0019] As a preferred solution, the organic wastewater includes at least one of organic complex wastewater, printing and dyeing wastewater, antibiotic wastewater, and garbage leachate.
[0020] As a preferred solution, the inorganic wastewater includes at least one of ammonia nitrogen wastewater and heavy metal wastewater;
[0021] As a preferred solution, the amount of the calcium iron magnesium composite catalytic material added to the organic wastewater or inorganic wastewater is regulated in the range of 0.1 to 4 g / L according to the content of pollutants to be oxidized and degraded in the organic wastewater or inorganic wastewater.
[0022] As a preferred solution, the amount of the hypochlorite added to the organic wastewater or inorganic wastewater is regulated in the range of 0.1 to 20 g / L according to the content of the pollutants to be oxidized and degraded in the organic wastewater or inorganic wastewater. It is well known to those skilled in the art that the amount of the calcium iron magnesium composite catalytic material and hypochlorite added to the organic or inorganic wastewater of the present invention is determined according to the content of the pollutants to be oxidized and degraded in the organic wastewater or inorganic wastewater. The higher the content of organic pollutants, the corresponding amount of the calcium iron magnesium composite catalytic material and hypochlorite added is also increased accordingly. Hypochlorite mainly provides hypochlorite, and any hypochlorite that can theoretically release hypochlorite can be used. However, it is best that its effective chlorine mass content is greater than 8%. Hypochlorites are conventional hypochlorites such as calcium hypochlorite and sodium hypochlorite.
[0023] As a preferred solution, the oxidation reaction conditions are: temperature of 5 to 40°C, time of more than 1 hour, pH of 5 to 11. Under alkaline conditions, it is more effective to improve the production of hypochlorous acid by calcium iron magnesium composite catalyst. 1 O 2 The catalytic activity of the active material is more preferably at a pH of 9 to 11.
[0024] The present invention is explained by taking calcium iron magnesium composite catalytic material catalyzing hypochlorite oxidation complex wastewater as an example. Complex wastewater, such as electroplating wastewater, has a main refractory organic matter as a transition metal complex, such as EDTA-Cu: the removal of EDTA-Cu occurs in an air bath constant temperature shaker, the reaction solution volume is 100mL, and the reaction is carried out at room temperature (25±5°C). The reaction process is: first add calcium iron magnesium composite catalytic material for adsorption reaction for 30 minutes, then add oxidant NaClO solution 3ml / L for catalytic oxidation removal for 90 minutes, sample in chronological order during the reaction, then filter the sample through a 0.22μm filter membrane, add sodium thiosulfate to quench, and store in an environment of 4°C.
[0025] The preparation method of the calcium iron magnesium composite catalyst provided by the present invention comprises the following steps:
[0026] (1) adding Ca salt, Mg salt and Fe salt in a ratio of 1 to 5:1:0.5 to 2.5 to distilled water and stirring to obtain a solution A with a mass concentration of 1 to 30%, slowly adding NaOH solution to the solution A during stirring to reach a stable pH of 7 to 11, and continuously stirring at a temperature of 5 to 40° C. for 0.5 to 3 hours to obtain a solution B;
[0027] (2) placing the solution B obtained in step (1) into a centrifuge at a centrifugal speed of 5000 to 15000 r / min to obtain a precipitate C;
[0028] (3) washing the precipitate C obtained in step (2) with distilled water and anhydrous alcohol solution for multiple times to obtain a precipitate D; the anhydrous alcohol solution is anhydrous ethanol, anhydrous propanol, etc.;
[0029] (4) placing the precipitate D obtained in step (3) into a vacuum drying oven for constant temperature drying at a temperature of 50 to 75° C. for a drying time of 10 to 20 h to obtain a dry solid E;
[0030] (5) Grinding the solid E obtained in step (4) into powder to obtain a calcium iron magnesium composite catalyst.
[0031] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0032] 1) The calcium iron magnesium composite catalyst provided by the present invention has good chemical stability, especially in the hypochlorite oxidation system, the material structure is stable and can be repeatedly used, and the repeated use effect is good, thereby reducing the use cost of the catalyst.
[0033] 2) The calcium iron magnesium composite catalyst provided by the present invention has high catalytic activity. When used to catalyze the oxidative degradation of pollutants in organic or inorganic wastewater with hypochlorite, the catalyst exhibits the characteristics of fast oxidative degradation rate, thorough oxidative degradation, high hypochlorite utilization rate, etc., and can well solve the problem of poor catalytic oxidation effect when the above-mentioned hypochlorite oxidation technology is applied to the removal of refractory organic matter in organic or inorganic wastewater.
[0034] 3) The calcium iron magnesium composite catalyst provided by the present invention does not need to use harmful transition metals or precious metal elements, which can avoid secondary pollution during the catalytic process and reduce the catalyst cost.
[0035] 4) The calcium-iron-magnesium composite catalyst provided by the present invention regulates the catalytic activity of the calcium-iron-magnesium composite catalyst by changing the doping amounts of calcium, magnesium and iron elements. When the calcium-iron-magnesium molar ratio is 4:1:2, the catalytic degradation effect of the calcium-iron-magnesium composite catalyst is better, and the composite catalyst has good chemical stability, which prevents dissolution, prolongs the service life of the catalyst, and can be recycled multiple times.
[0036] 5) The preparation method of the calcium iron magnesium composite catalyst provided by the present invention is low in cost, simple in method, has low requirements on equipment and good operability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention is a flow chart of the preparation process of the calcium iron magnesium composite catalyst.
[0038] Figure 2 This is a comparison chart of the pollutant degradation effects of the calcium iron magnesium composite catalyst prepared under different conditions in Examples 2 to 7.
[0039] Figure 3 This is the SEM image of the calcium iron magnesium composite catalyst prepared in Example 1 at 1 μm.
[0040] Figure 4 This is the infrared spectrum of the calcium iron magnesium composite catalyst prepared in Example 1.
[0041] Figure 5 This is the XPS test chart of the calcium iron magnesium composite catalyst prepared in Example 1.
[0042] Figure 6 This is the XRD test pattern of the calcium iron magnesium composite catalyst prepared in Example 1.
[0043] Figure 7The pollutant removal rate of the calcium iron magnesium composite catalyst prepared in Example 1 at different catalyst dosages.
[0044] Figure 8 The pollutant removal rate of the calcium iron magnesium composite catalyst prepared in Example 1 at different oxidant dosages.
[0045] Fig. 9 The removal rate of pollutants by the calcium iron magnesium composite catalyst prepared in Example 1 at different times.
[0046] Fig.10 This is a free radical quenching experiment of the calcium iron magnesium composite catalyst prepared in Example 1. DETAILED DESCRIPTION
[0047] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the protection scope of the claims of the present invention is not limited to this embodiment.
[0048] Example 1
[0049] (1) adding calcium nitrate, calcium chloride and magnesium chloride to distilled water and stirring to obtain a solution A with a total mass percentage concentration of 10%, wherein the molar ratio of calcium element to iron element to magnesium element in solution A is 4:1:2, adding NaOH solution to solution A during stirring to stabilize the pH at 11, and continuously stirring at 20° C. for 2 hours to obtain solution B, wherein the solution is a uniform suspension;
[0050] (3) washing the solution B obtained in step (2) with distilled water and anhydrous ethanol for multiple times, and collecting the solution at 10,000 r / min to obtain a precipitate C;
[0051] (4) placing the precipitate C obtained in step (3) into a vacuum drying oven at 60° C. for constant temperature drying for 12 hours to obtain a dry solid D, which is a reddish brown solid;
[0052] (5) Grinding the solid D obtained in step (4) into powder to obtain a calcium iron magnesium composite catalyst.
[0053] (6) The calcium iron magnesium composite catalytic material was applied to the electroplating wastewater with EDTA-Cu of 20 mg / L for degradation. 2+The concentration of calcium iron magnesium composite catalyst is 20mg / L, the amount of calcium iron magnesium composite catalyst material added is 0.5g / L, the amount of sodium hypochlorite solution with a concentration of 1mol / L added is 3mL / L, and the conditions of oxidative degradation are: room temperature, 90min1 hour, pH 11. At the same time, different calcium iron magnesium composite catalyst material addition amounts of 0, 0.5, 0.25, and 0.75g / L were investigated for comparison; the amount of sodium hypochlorite solution added was 1 and 2mL / L for comparison; and the time was 15, 30, 45, 60, and 75min for comparison.
[0054] The calcium iron magnesium composite catalyst prepared in Example 1 was subjected to various tests.
[0055] from Figure 3 It can be seen from the electron microscope image that the prepared calcium iron magnesium composite catalyst has a layered block structure, which improves the agglomeration phenomenon of ferrihydrite and makes it have a more stable structure.
[0056] from Figure 4 See that 576cm -1 The absorption peaks near 668cm are caused by the stretching vibration of Fe-O and Ca-O bonds. -1 The absorption peak near 1152cm is caused by the stretching vibration of Mg-O bond. -1 The absorption peak nearby is caused by the sulfate on the surface of the material that has not been washed off, 1371cm -1 The absorption peak near 1619cm is caused by the stretching vibration of Fe-OH bond; -1 The absorption peak that appears nearby is the HOH deformation vibration peak, 3399cm -1 The bands are related to the stretching vibration of the surface hydroxyl group, the -OH vibration of the adsorbed water, and the bending vibration of Fe-OH. Therefore, combined with the spectrum analysis, it can be seen that the doping of Ca and Mg elements breaks some Fe-OH bonds, forms some Ca-O and Mg-O bonds, and generates oxygen vacancies. During the synthesis of the material, the incorporation of Ca promotes the release of lattice oxygen, increases the utilization rate of lattice oxygen, forms a large number of oxygen vacancies and defects, and thus improves the catalytic performance of the material.
[0057] from Figure 5The Fe2p spectrum shows two pairs of spin-orbit doublets, which contain Fe(Ⅱ) and Fe(Ⅲ). The peaks at 710.8eV and 724.5eV are due to the core energy level of Fe(Ⅱ), and the binding energy at 713.5eV and 734.6eV are attributed to the existence of Fe(Ⅲ). The peaks at 346.9eV and 351eV in the Ca 2p spectrum represent Ca2p3 / 2 and Ca2p1 / 2, indicating that the Ca element has been successfully introduced into the material, releasing part of the lattice oxygen and generating oxygen vacancies. In the Mg1s spectrum, the peak at 1303eV indicates that the Mg element has been successfully introduced into the material. In the O1s spectrum, the three fitting peaks at 529.5eV, 531.2eV, and 532.8eV can be attributed to the lattice oxygen bound to the metal and the adsorbed oxygen on the oxygen vacancies, respectively. The incorporation of Ca leads to a reduction in lattice oxygen, which is converted into adsorbed oxygen on oxygen vacancies. The oxygen species adsorbed on oxygen vacancies can stabilize the oxygen vacancies, and the abundant oxygen vacancies can increase the electron transfer ability of the material surface, thereby improving the catalytic performance.
[0058] In order to explore the effect of Ca and Mg doping on the physical and chemical properties of the catalytic material, X-ray diffraction (XRD) was used to study the changes in the crystal structure of the material after the addition of Ca and Mg elements. The XRD energy spectrum of the catalytic material before and after Ca and Mg doping showed a diffraction pattern similar to that of ferrihydrite, which indicates that the addition of Ca and Mg elements did not change the original crystal structure of the catalytic material. Figure 6 It can be seen that the peaks at 2θ of 24.1°, 33.1°, and 49.1° correspond to Ca-OH (PDF#99-0060) and its (012), (104), and (110) crystal planes, the peak at 2θ of 29.4° is related to Ca-O (PDF#28-0775), and the diffraction peaks at 38.4°, 44.3°, and 59.1° through (PDF#30-0974) belong to Mg (222) plane, Mg (400) plane, and Mg (511) plane, respectively. The enhancement of these peaks indicates that the crystallinity and particle size increase due to the incorporation of Ca and Mg.
[0059] The calcium iron magnesium composite catalyst prepared in Example 1 was applied to the removal of complexed heavy metals in electroplating wastewater, wherein the amount of the catalyst was 0.5 g / L, and complexed copper was used instead of electroplating wastewater for the experiment. 2+ The concentration of the Figure 7 , Figure 8 , Fig. 9 It can be seen that when the oxidant dosage is 3ml / L, a removal effect of 97.5% can be achieved in 90 minutes.
[0060] There are many active substances in the hypochlorous acid oxidation system, including hydroxyl radicals (·OH), superoxide radicals (O 2-), singlet oxygen ( 1 O 2 ) and active chlorine (Cl·, ClO·), etc. The free radical shielding experiment results are as follows Fig.10 As shown, ascorbic acid, L-histidine, methanol, tert-butyl alcohol, p-benzoquinone and other agents were added to mask non-free radicals and free radicals, 1 O 2 , ·OH and Cl·, ·OH, O 2- The experiment explored the active substances that contributed to the reaction system based on the Cu removal rate.
[0061] When ascorbic acid, which has a masking effect on almost all ROS, is added to the reaction system, the removal reaction of Cu is completely inhibited, and the final removal rate of Cu is only 9.1%. When masking agents L-histidine and p-benzoquinone are added to the reaction system, the removal rates of Cu are only 4.5% and 5.6%. However, when masking agents methanol and tert-butanol are added to the reaction system, the removal rate of Cu is not significantly affected, and can still reach 98.9% and 98.5%. Therefore, it can be judged that the main active species in the system are 1 O 2 , the role of other active species in the system can be ignored.
[0062] Therefore, the present invention adopts the above-mentioned structure to prepare a calcium iron magnesium composite catalyst for degrading pollutants in electroplating wastewater. The preparation method of the calcium iron magnesium composite catalyst is simple, has low equipment requirements, good operability, stable material structure in the hypochlorous acid oxidation system, and good reuse effect.
[0063] Example 2
[0064] The difference between Example 2 and Example 1 is that the reaction pH is replaced with 7 and 9 respectively, which is compared with 11 in Example 1. The calcium iron magnesium composite catalytic material is applied to electroplating wastewater with EDTA-Cu of 20 mg / L for degradation. 2+ The concentration of calcium iron magnesium composite catalyst material was 20 mg / L, the amount of calcium iron magnesium composite catalyst material added was 0.5 g / L, and the amount of sodium hypochlorite solution with a concentration of 1 mol / L was 3 mL / L. The conditions for oxidative degradation were: room temperature, 90 min 1 hour, and pH 11. Results are shown in Figure 2 .
[0065] Example 3
[0066] The difference between Example 3 and Example 1 is that the molar ratios of calcium, iron and magnesium are replaced with 1:1:2, 2:1:2, 3:1:2 and 5:1:2 respectively, which is compared with 4:1:2 in Example 1. The calcium iron magnesium composite catalytic material is applied to electroplating wastewater containing 20 mg / L EDTA-Cu for degradation. The complex copper (Cu 2+ The concentration of calcium iron magnesium composite catalyst material was 20 mg / L, the amount of calcium iron magnesium composite catalyst material added was 0.5 g / L, and the amount of sodium hypochlorite solution with a concentration of 1 mol / L was 3 mL / L. The conditions for oxidative degradation were: room temperature, 90 min 1 hour, and pH 11. Results are shown in Figure 2 .
[0067] Example 4
[0068] The difference between Example 4 and Example 1 is that the reaction temperature is replaced by 40°C and 60°C respectively, which is compared with 20°C in Example 1. The calcium iron magnesium composite catalytic material is applied to electroplating wastewater containing 20 mg / L EDTA-Cu for degradation. The complex copper (Cu 2+ The concentration of calcium iron magnesium composite catalyst material was 20 mg / L, the amount of calcium iron magnesium composite catalyst material added was 0.5 g / L, and the amount of sodium hypochlorite solution with a concentration of 1 mol / L was 3 mL / L. The conditions for oxidative degradation were: room temperature, 90 min 1 hour, and pH 11. Results are shown in Figure 2 .
[0069] Example 5
[0070] The difference between Example 5 and Example 1 is that the reaction time is replaced by 4h and 6h respectively, which is compared with 2h in Example 1. The calcium iron magnesium composite catalytic material is applied to electroplating wastewater with EDTA-Cu of 20mg / L for degradation. 2+ The concentration of calcium iron magnesium composite catalyst material was 20 mg / L, the amount of calcium iron magnesium composite catalyst material added was 0.5 g / L, and the amount of sodium hypochlorite solution with a concentration of 1 mol / L was 3 mL / L. The conditions for oxidative degradation were: room temperature, 90 min 1 hour, and pH 11. Results are shown in Figure 2 .
[0071] Example 6
[0072] The difference between Example 6 and Example 1 is that the molar ratios of calcium, iron and magnesium are 4:1:0.5, 4:1:1, 4:1:1.5 and 4:1:2.5 respectively, which is compared with 4:1:2 in Example 1. The calcium iron magnesium composite catalytic material is applied to electroplating wastewater containing 20 mg / L EDTA-Cu for degradation. The complex copper (Cu 2+The concentration of calcium iron magnesium composite catalyst material was 20 mg / L, the amount of calcium iron magnesium composite catalyst material added was 0.5 g / L, and the amount of sodium hypochlorite solution with a concentration of 1 mol / L was 3 mL / L. The conditions for oxidative degradation were: room temperature, 90 min 1 hour, and pH 11. Results are shown in Figure 2 .
[0073] Example 7
[0074] The difference between Example 7 and Example 1 is that the molar ratio of calcium, iron and magnesium is 4:1:0, which is compared with 4:1:2 in Example 1. The calcium-iron composite catalytic material or the calcium-iron-magnesium composite catalytic material is applied to electroplating wastewater containing 20 mg / L EDTA-Cu for degradation. The complex copper (Cu 2+ The concentration of the catalyst was 20 mg / L, the amount of calcium iron composite catalyst material / calcium iron magnesium composite catalyst material added was 0.5 g / L, and the amount of sodium hypochlorite solution with a concentration of 1 mol / L was 3 mL / L. The conditions for oxidative degradation were: room temperature, 90 min 1 hour, and pH 11. Results are shown in Figure 2 .
[0075] By recycling the calcium iron composite catalytic material or the calcium iron magnesium composite catalytic material and recycling it according to the above degradation process, the recycling effect can be seen in Figure 2 It can be seen that magnesium doping significantly improves its chemical stability.
[0076] Example 8
[0077] The calcium iron magnesium composite catalyst of Example 1 was used to degrade tetraaminopyridine wastewater: the ammonia nitrogen removal experiment took place in an air bath constant temperature shaker, the reaction solution volume was 100mL, the tetraaminopyridine concentration was set to 200mg / L and the reaction was carried out at room temperature (25±5°C). The reaction process was: first add 0.5 / L catalytic material, then add 5ml / L of oxidant sodium hypochlorite solution for oxidation removal for 90min, take samples, and measure.
[0078] Example 9
[0079] The calcium iron magnesium composite catalyst of Example 1 was used to degrade ammonia nitrogen wastewater: the ammonia nitrogen removal experiment took place in an air bath constant temperature shaker, the reaction solution volume was 100 mL, the ammonia nitrogen concentration was set to 50 mg / L and the reaction was carried out at room temperature (25±5°C). The reaction process was: first add 0.5 / L catalytic material, then add oxidant calcium hypochlorite 1g / L for oxidation removal for 90 minutes, take samples, and measure.
[0080] Example 10
[0081] The calcium iron magnesium composite catalyst of Example 1 was used to degrade landfill leachate wastewater: COD removal experiment took place in an air bath constant temperature shaker, the reaction solution volume was 100 mL, the COD concentration was set to 2655 mg / L and the reaction was carried out at room temperature (25±5°C). The reaction process was: first add 0.5 / L catalytic material, then add 5 ml / L of oxidant sodium hypochlorite solution for oxidation removal for 90 minutes, take samples, and measure.
[0082] Table 1 is the results of treating pollutants in different wastewaters with iron-calcium-magnesium catalysts in Example 2
[0083]
[0084]
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a calcium iron magnesium composite catalyst, characterized in that: Calcium salt, magnesium salt and iron salt are dissolved in water, and then a strong alkaline solution is added to carry out a hydrolysis co-precipitation reaction. The obtained precipitated product is successively centrifuged, washed, dried and ground to obtain the product.
2. The method for preparing a calcium iron magnesium composite catalyst according to claim 1, characterized in that: The molar ratio of the calcium salt, the iron salt and the magnesium salt is 1-5:1:0.5-2.
5.
3. The method for preparing a calcium iron magnesium composite catalyst according to claim 1 or 2, characterized in that: The total mass percentage concentration of the calcium salt, magnesium salt and iron salt in water is 1-30%.
4. The method for preparing a calcium iron magnesium composite catalyst according to claim 1 or 2, characterized in that: The calcium salt includes at least one of calcium nitrate, calcium hypochlorite and calcium chloride; The magnesium salt includes at least one of magnesium nitrate, magnesium sulfate and magnesium chloride; The iron salt includes at least one of ferric chloride, ferric sulfate and ferric nitrate.
5. The method for preparing a calcium iron magnesium composite catalyst according to claim 1, characterized in that: The conditions of the hydrolysis coprecipitation reaction are: adding a strong alkaline solution to maintain the pH at 7-11, stirring the reaction at 5-40° C. for 0.5-3 hours.
6. The method for preparing a calcium iron magnesium composite catalyst according to claim 1, characterized in that: The drying is carried out in a vacuum drying manner, the drying temperature is 50-100° C., and the drying time is 10-20 hours.
7. A calcium iron magnesium composite catalyst, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 6.
8. The use of a calcium iron magnesium composite catalyst according to claim 7, characterized in that: Used to catalyze the oxidative degradation of organic and / or inorganic wastewater by hypochlorite.
9. The use of a calcium iron magnesium composite catalyst according to claim 8, characterized in that: The organic wastewater includes at least one of organic complex wastewater, printing and dyeing wastewater, antibiotic wastewater, and garbage leachate; The inorganic wastewater includes at least one of ammonia nitrogen wastewater and heavy metal wastewater; The amount of the calcium iron magnesium composite catalyst material added to the organic wastewater or inorganic wastewater is regulated within the range of 0.1 to 4 g / L according to the content of the pollutants to be oxidized and degraded in the organic wastewater or inorganic wastewater; The amount of the hypochlorite added to the organic wastewater or inorganic wastewater is regulated within the range of 0.1 to 20 g / L according to the content of pollutants to be oxidized and degraded in the organic wastewater or inorganic wastewater.
10. The use of a calcium iron magnesium composite catalyst according to claim 8, characterized in that: The conditions for the oxidative degradation are: temperature of 5-40° C., time of more than 1 hour, and pH of 5-11.